1994
DOI: 10.1111/j.1365-2621.1994.tb08193.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Hydrolysate and Antistaling Amylase Effects on Retrogradation of Starch in Bread

Abstract: Effects of phospholipid hydrolysate and antistaling amylase on starch retrogradation in bread and wheat flour were investigated by differential scanning calorimetry @SC). Phospholipid hydrolysate containing more than 90% lysophospholipid was obtained using phospholipase A, and was effective in formine amvlose-lioid comnlexes. Both wheat flour and ABSTtiCT bread containing phospuholipid hydiolysate fere retrograded to a lesser degree when stored at room temperature. The retrogradation rate for bread with antist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…Del-Rosario and Pontiveros (1983) reported that from soft to hard of texture may curtail the storage life and lower product value. For all starchy foods, including bread, retrogradation is a definite phenomenon (Kweon et al, 1994). Thus, the bread quality can be extremely affected and therefore restrict its popularization and adoption (Huang et al, 1988).…”
Section: Bread Quality Improvement By Means Of Selected Pregelatinizementioning
confidence: 99%
See 2 more Smart Citations
“…Del-Rosario and Pontiveros (1983) reported that from soft to hard of texture may curtail the storage life and lower product value. For all starchy foods, including bread, retrogradation is a definite phenomenon (Kweon et al, 1994). Thus, the bread quality can be extremely affected and therefore restrict its popularization and adoption (Huang et al, 1988).…”
Section: Bread Quality Improvement By Means Of Selected Pregelatinizementioning
confidence: 99%
“…Many techniques to improve starchy foods' quality and delay retrogradation were found by researchers such as the addition of selected starch (Huang et al, 1988), emulsifier (Rao et al, 1992) or enzyme (Kweon et al, 1994). For emulsifier, it can effectively prolong starch colloid hardening and defer staling and retrogradation rate (Keetels et al, 1996).…”
Section: Bread Quality Improvement By Means Of Selected Pregelatinizementioning
confidence: 99%
See 1 more Smart Citation
“…PLs are used throughout the world to improve the functional properties in food processing: improvement in bread texture and volume, dough tolerance, baking properties, and to retard bread becoming state (Kweon et al, 1994;Lin & Czuchajowska, 1998). For this reason, the present study focused on the usefulness of PUFA-PLs as a bread ingredient affecting the thermal and physical properties of starch in dough and bread during mixing, baking, and maintaining an excellent quality.…”
mentioning
confidence: 99%
“…PLs are used throughout the world to improve food processing, such as clarifying starch pastes (5), enhanc lug the viscosity of starch, increasing dough tolerance, and improving baking properties (6)(7). For this reason, the present study was focused on the preparation of PUFA-PLs by lipase-catalyzed transesterification be tween purified egg PLs and concentrated PUFAs from menhaden oil, and on their usefulness for starch pro cessing in relation to gelatinization or retrogradation.…”
mentioning
confidence: 99%